Malocclusions in primary and early mixed dentition in very preterm children - Maaniitty Elina; Vahlberg Tero; Lüthje Petra; Rautava Päivi; Svedström-Oristo Anna-Liisa (TAYLOR & FRANCIS LTD, 2022)
Objective: To compare the prevalence of malocclusions in the primary and early mixed dentition of very preterm and full-term children. Material and methods: Study subjects consisted of 205 very preterm (90 girls and 115 boys), and 205 age- and gender-matched full-term children. Data were collected from the register of Turku University Hospital (children born before the 37th week of pregnancy with a birth weight of less than 1500 g, and all infants born before the 32nd week of pregnancy) and from public health centre dental registers. Results: In primary dentition, case children had a higher odds of dental crowding (OR = 2.94, 95% CI 1.17-7.35, p = .021), a tendency toward increased overbite (OR = 1.55, 95% CI 0.93-2.59, p = .096), and a lower odds of increased overjet (OR = 0.19, 95% CI 0.07-0.57, p = .003) compared to control children. In early mixed dentition, there were no statistically significant differences in occlusal traits; however, case children were significantly more likely to have received orthodontic treatment (OR = 2.80, 95% CI 1.50-5.23, p = .001) compared to controls. Conclusions: The results indicate that in primary dentition, the prevalence of malocclusion varies between very preterm and full-term children. In early mixed dentition, the distribution of occlusal traits is more similar.